2017
DOI: 10.1080/13607863.2017.1286453
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders among older prisoners: a systematic review and comparison study against older people in the community

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 44 publications
2
57
0
2
Order By: Relevance
“…All the studies reported on female patients as well. This was welcome, as thus far, research in other forensic settings (eg, prisons) has often failed to include female samples, 25 Our findings also evidenced frequent previous admission to forensic psychiatric services, very long-stay in secure units, and mixed feelings about the benefits of the activities and rehabilitation programmes currently available for the ageing patients. This all seems to suggest that the unique complex needs of this populations may not be fully met in the current service provision, thus requiring further debate on potential ways to improve the system, such as the development of dedicated services for ageing patients.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…All the studies reported on female patients as well. This was welcome, as thus far, research in other forensic settings (eg, prisons) has often failed to include female samples, 25 Our findings also evidenced frequent previous admission to forensic psychiatric services, very long-stay in secure units, and mixed feelings about the benefits of the activities and rehabilitation programmes currently available for the ageing patients. This all seems to suggest that the unique complex needs of this populations may not be fully met in the current service provision, thus requiring further debate on potential ways to improve the system, such as the development of dedicated services for ageing patients.…”
Section: Discussionmentioning
confidence: 63%
“…We note that all studies, except for one that does not report this information, included female patients in their investigation, despite women representing the minority of patients. This is in contrast with research in other restrictive settings (ie, prisons), which traditionally focus on male samples …”
Section: Quality Appraisalmentioning
confidence: 82%
See 2 more Smart Citations
“…In relation to mental health, a recent meta‐analysis found that 38% of ageing prisoners suffer from ‘any psychiatric disorder’, with more than double the prevalence reported in community studies (15%) (Di Lorito, Vӧllm, & Dening, ). The authors also found higher prevalence for depression, schizophrenia/psychoses and anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%